El papel de la UE en las reformas del sistema judicial - Matić Bošković, Marina; Kostić, Jelena (REVISTA ELECTRONICA IBEROAMERICANA, 2024)
The European Union plays a significant role in reforming the judicial system, both in countries aspiring to EU membership and in existing EU member states. Achieving an adequate level of judicial independence, accountability, professionalism, and efficiency is crucial for preserving the rule of law across the EU. To this end, the European Union employs various mechanisms, initiatives, and corrective measures. These are essential not only for supporting judicial reforms but also for monitoring and evaluating the implementation of the recommendations provided.The aim of this paper is to highlight the importance of the European Union’s role in supporting judicial reform in both member states and countries aspiring to EU membership. To achieve this, the authors analyze European standards relevant to the independence, impartiality, and efficiency of the judiciary, as well as various mechanisms, reports, and opinions from relevant bodies. This approach allows authors to identify not only the challenges observed but also examples of good practices that can be valuable for both member states and candidate countries seeking EU membership.